IMPORTANCE, MAIN FUNCTIONS AND OBJECTIVES OF COST ACCOUNTING (Euro-Asia Conferences, 2021)
This article substantiates the need to improve the regulation on costs. Main functions, objectives and importance are presented. Suggestions for improving cost accounting are presented.